2014
DOI: 10.18632/oncotarget.2191
|View full text |Cite
|
Sign up to set email alerts
|

SHP-1 is a target of regorafenib in colorectal cancer

Abstract: Regorafenib is an inhibitor of multiple protein kinases which exerts antitumor and antimetastatic activities in metastatic colorectal cancer (CRC). SH2 domain-containing phosphatase 1 (SHP-1) is reported to have tumor suppressive potential because it acts as a negative regulator of p-STAT3Tyr705 signaling. However, little is known about the mechanism regarding regorafenib affects SHP-1 tyrosine phosphatase activity and leads to apoptosis and tumor suppression in CRC. Here, we found that regorafenib triggered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 25 publications
6
49
1
2
Order By: Relevance
“…Therefore, on the basis of the findings detailed in the present study, the present authors hypothesize that SHP-1 contributes to EGCG-induced apoptosis by modifying the phosphorylation patterns of key apoptosis regulators, including p38α MAPK. Although a number of agonists and inhibitors of SHP-1 have been employed to treat solid tumors, these treatments are rarely used for leukemia (11,12). The finding that SHP-1 affects apoptosis in NB4 cells suggests that agonists and inhibitors of SHP-1, either alone or combination with EGCG, may also be used to treat leukemia in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, on the basis of the findings detailed in the present study, the present authors hypothesize that SHP-1 contributes to EGCG-induced apoptosis by modifying the phosphorylation patterns of key apoptosis regulators, including p38α MAPK. Although a number of agonists and inhibitors of SHP-1 have been employed to treat solid tumors, these treatments are rarely used for leukemia (11,12). The finding that SHP-1 affects apoptosis in NB4 cells suggests that agonists and inhibitors of SHP-1, either alone or combination with EGCG, may also be used to treat leukemia in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A number of agonists and inhibitors of SHP-1 have been applied in clinical cancer therapies. For example, γ-tocotrienol (11) and regorafenib (12) have been used to treat breast tumors and colorectal cancer, respectively. Studies have reported that SHP-1 is highly expressed in normal hematopoietic cells (13) but weakly expressed in hematological malignancies, including Burkitt's lymphoma (14), APL (15) and chronic myeloid leukemia (16).…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical value of cancer treatment by targeting SHP-1 is still under investigation. According to a few reports [50][51][52], several agents that regulate SHP-1 activity have been identified, and some have found efficacy against different cancer cells. In our previous work, we disclosed that regorafenib, a multiple protein kinase inhibitor, exerts anti-tumor effects by enhancing SHP-1 activity [50].…”
Section: Discussionmentioning
confidence: 99%
“…According to a few reports [50][51][52], several agents that regulate SHP-1 activity have been identified, and some have found efficacy against different cancer cells. In our previous work, we disclosed that regorafenib, a multiple protein kinase inhibitor, exerts anti-tumor effects by enhancing SHP-1 activity [50]. Dovitinib, another multiple protein kinase inhibitor, acts as a novel radiosensitizer in HCC by upregulating SHP-1 [51].…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of STAT3 promotes proliferation and invasiveness of human glioblastoma cells [13]. In particular, highly expressed phosphorylated (p)-STAT3 in cancer cell plays an essential role in the progression of cancer via downregulation by SHP-1 [15]. Therefore, in the current study, we tried to explore the underlying molecular mechanism of VB in glioblastoma involving SHP-1 and STAT3.…”
Section: Introductionmentioning
confidence: 99%